View of steps and adhisthana from the entrance - Temples of India Project Team (Jio Institute, 2024)
Moonstone and steps leading up to the first level are visible from the approach, specifically from the east side coming from the Chand Baori. Seats for visitors were added as part of the site’s restoration by the Archaeological Survey of India (ASI). Two moonstones are visible. One is placed at the base of the steps (foreground) on the ground level and a smaller moonstone is present on the third step.